Immobilization of a nonsteroidal antiinflammatory drug onto commercial segmented polyurethane surface to improve haemocompatibility properties - Abraham, Gustavo Abel (2002)
A method has been developed in which a layer of p-aminosalicylic acid (4-amino-2-hydroxybenzoic acid) (PAS), a water soluble pharmaceutical compound of the nonsteroidal anti-inflammatory drug (NSAID) class with antiaggregant platelet activity, is covalently immobilized onto a segmented polyurethane, Biospan™ (SPU) surface. Thus, SPU surfaces were modified by grafting of hexamethylenediisocyanate, and the free isocyanate remaining on the SPU surface were then coupled through a condensation reaction to amine groups of p-aminosalicylic acid. The bonding of PAS from aqueous solution onto SPU surface was studied by ATR-FTIR, UV and fluorescence spectroscopy. Plateau levels of coupled PAS were reached within 1.2μg/cm2 using PAS solution concentrations of 1mg/ml. The surface wettability of the polymeric films measured by contact angle indicate that the introduction of the PAS turns the surface more hydrophilic (θwater=43.1°±2.1°) relatively to the original SPU films (θwater=70.3°±1.9°). The in vitro albumin (BSA) adsorption shows that the PAS-SPU films adsorb more BSA (250/μgmm2) than the original SPU (112μg/mm2). Thrombogenicity was assessed by measuring the thrombus formation and platelet adhesion of the SPU containing PAS relatively to nonmodified SPU surfaces. The polymeric surfaces with immobilized PAS had better nonthrombogenic characteristics as indicated by the low platelet adhesion, high adsorption of albumin relatively to fibrinogen and low thrombus formation, making them potentially good candidates for biomedical applications. © 2002 Elsevier Science Ltd. All rights reserved.